Hubungan Antara Task Aversiveness dengan Prokrastinasi Akademik pada Mahasiswa di Universitas X - Nastasia, Krisnova; Mujidin (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
After completing high school education, many decide to choose to continue on to college. When you become a student, there will definitely be lots of assignments, obligations and challenges faced in order to complete your studies to completion, so it's not surprising that many students experience task aversiveness. Task aversiveness greatly affects the academic procrastination of students. This study aims to determine the relationship between task aversiveness and academic procrastination final assignments on students in the tourism department of hospitally management study program, faculty of tourism and hospitally class of 2017-2018 Univeritas Negeri Padang. This study used a quantitative approach with a correlation method. The measuring instrument used in this study was task aversiveness scale and academic procrastination scale. The population in this study was student at tourism department of hospitally management study program, the sampel was 112 students of the tourism department of hospitally management study program, faculty of tourism and hospitally class of 2017-2018 Universitas Negeri Padang. this study used probability sampling method with simple random sampling technique. Data analysis was carried out used the rho (ρ) correlation thecniques. The results showed that the correlation coefficient of rho (ρ) is 0,410 with a (ρ) is 0,000. This showed that there was very significant positive relationship between task aversiveness and academic procrastination students in the tourism department of hospitally management study program, faculty of tourism and hospitally class of 2017-2018 Universitas Negeri Padang. It means that the higher the task aversiveness, the higher the academic procrastination and the lower the task aversiveness, the lower the academic procrastination. The effective contribution of the task aversiveness variable to the academic procrastination variable is 17%.